Islamic perceptions of medication with special reference to ordinary and extraordinary means of medical treatment - Malik, Mohammad Manzoor (Bangladesh Bioethics Society (BBS), 2013)

(untitled)
This study attempts an exposition of different perceptions of obligation to medical treatment that have emerged from the Islamic theological understanding and how they contribute to diversity of options and flexibility in clinical practice. Particularly, an attempt is made to formulate an Islamic perspective on ordinary and extraordinary means of medical treatment. This distinction is of practical significance in clinical practice, and its right understanding is also important to public funded healthcare authorities, guardians of the patients, health and life insurance institutions, and employers who provide health care coverage to their employees. Not only these parties, but also lawyers and justice administration functionaries such as public prosecutors and judges are in need of understanding this distinction to deal with relevant litigations. The distinction could be made regarding terminally ill patients and non-terminally ill patients separately. The essential factors that matter in making the distinction between ordinary and extraordinary means of treatment are: (1) patient capacity (2) expert advice, and (3) nature of medication. Regarding terminally ill patients, medical treatment can become extraordinary because of (1) patient capacity and (2) nature of medication. In both these case the deciding condition applies: the expert advice taken from a group of physicians. In regards to non- terminally ill patients, extraordinary medical treatment includes three cases: (1) treatment that is known to be useless and futile, (2) treatment that endangers the life or cause more harm than what it removes, and (3) useful treatment, but the patient is unable to bear the cost.